Negative Regulation of Violacein Biosynthesis in Chromobacterium violaceum - Devescovi, Giulia; Kojic, Milan; Covaceuszach, Sonia; Cámara, Miguel; Williams, Paul; Bertani, Iris; Subramoni, Sujatha; Venturi, Vittorio (Frontiers in Microbiology, 2017)
In Chromobacteium violaceum, the purple pigment violacein is under positive regulation by the N-acylhomoserine lactone CviI/R quorum sensing system and negative regulation by an uncharacterized putative repressor. In this study we report that the biosynthesis of violacein is negatively controlled by a novel repressor protein, VioS. The violacein operon is regulated negatively by VioS and positively by the CviI/R system in both C. violaceum and in a heterologous Escherichia coli genetic background. VioS does not regulate the CviI/R system and apart from violacein, VioS and quorum sensing regulate other phenotypes antagonistically. Quorum sensing regulated phenotypes in C. violaceum are therefore further regulated providing an additional level of control.